Industrial design: latitudine e longitudine Una prima lezione - Tonelli, Maria Cristina (Studi e saggi, 2008)
The first lesson on industrial design has to address questions such as «what is industrial design?» «what are its relations with the world of production?» «in what way does it change our perception of objects?». By now the word «design» is a part of our language used - relevantly, superficially or casually - to qualify myriad aspects of everyday experience. However the semantic elasticity of the term conceals a professional practice, a decision-making process and a productive research the results of which have profoundly affected our society and our lives. A designer does not simply design an object. Through the object he or she also conditions the physical and emotional scenario of the people who use it. Just as industry does not simply offer goods, but distributes culture or non-culture through its choices of product design. Explaining what this creative activity consists of, which spheres it comprises, who are the actors and what skills are required of them, this book aims to provide critical tools and stimulate further study.